2001
DOI: 10.1074/jbc.m005960200
|View full text |Cite
|
Sign up to set email alerts
|

RNA CUG Repeats Sequester CUGBP1 and Alter Protein Levels and Activity of CUGBP1

Abstract: An RNA CUG triplet repeat binding protein, CUGBP1, regulates splicing and translation of various RNAs. Expansion of RNA CUG repeats in the 3-untranslated repeat of the mutant myotonin protein kinase (DMPK) mRNA in myotonic dystrophy (DM) is associated with alterations in binding activity of CUGBP1. To investigate whether CUGBP1 is directly affected by expansion of CUG repeats in DM tissues, we examined the intracellular status of CUGBP1 in DM patients as well as in cultured cells over expressing RNA CUG repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
272
2
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(290 citation statements)
references
References 29 publications
10
272
2
5
Order By: Relevance
“…CUGBP1 was detected with polyclonal antibodies against CUGBP1 (1:1000) as described. 14 To determine protein loading, the same membrane after CUGBP1 detection was reprobed with antibodies against b-actin, and CUGBP1 levels were calculated as ratio to b-actin.…”
Section: Western Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…CUGBP1 was detected with polyclonal antibodies against CUGBP1 (1:1000) as described. 14 To determine protein loading, the same membrane after CUGBP1 detection was reprobed with antibodies against b-actin, and CUGBP1 levels were calculated as ratio to b-actin.…”
Section: Western Analysismentioning
confidence: 99%
“…[2][3][4] At the molecular levels, the DM1 phenotype is most likely caused by a complex molecular pathogenesis, including deficiency of myotonic dystrophy myotonin kinase (DMPK) protein, [5][6][7] haplo-insufficiency of a neighboring homeobox gene (particular the DM locus-associated homeodomain protein (DMAHP/Six 5 gene) 8 and the WD-repeat gene (DMWD) 9 and a trans-dominant misregulation of RNA homeostasis. [10][11][12][13][14][15][16] Recent experiments from transgenic mice, expressing an untranslated expanded CUG repeat under the control of the human skeletal actin promoter, showed that expanded CUG repeats are sufficient to generate DM1 muscle phenotype. 17 These data suggest that misregulation of RNA homeostasis may play a major role in DM1 muscle pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…One of the members of the CUGBP family, CUGBP1, contributes to at least three symptoms of DM1: the delay of skeletal muscle differentiation (12), myotonia (19), and the insulin resistance (13). Previous studies showed that the expansion of CUG repeats in DM1 leads to a 3-5-fold elevation of CUGBP1 binding activity and protein levels (13, 19 -21), perhaps by stabilizing CUGBP1 protein within RNA CUG-CUGBP1 complexes (21). CUGBP1 possesses two major biological functions: regulation of splicing and translation (12, 20 -22).…”
Section: Dm1mentioning
confidence: 99%
“…The main problem of this strategy is low stability of siRNA and lack of efficient delivery systems of these reagents. 12,13 The complex proposed in our study should effectively bind and stabilise siRNA for transfection and should show low toxicity for a variety of cells. For the lactose based surfactants chosen (LA12), the bonding of lactose moiety with the hydrophobic fragment via an amine group ensures effective proton bonding in acidic environment, which means that they can act as cationic surfactants.…”
mentioning
confidence: 99%
“…The sequence studied is responsible for silencing the gene that can be important in therapy of myotonic dystrophy type 1 (DM1). [11][12][13] DM1 is the most frequent form of muscular dystrophy in adults. 14 It is an autosomal-dominant hereditary disease which can affect many tissues and produce diverse symptoms, including muscle hyperactivity (myotonia), progressive myasthenia, heart conduction defects, cardiomyopathy, insulin resistance, or neuropsychological disturbances.…”
mentioning
confidence: 99%